Adaptation of Islamic Religious Education for Children of Migrant Workers in Pesantren - Moh. Elman; Sulalah Sulalah; M Samsul Hady (JUMPA : Jurnal Manajemen Pendidikan, 2026)
This article aims to explore the adaptive patterns of Islamic Religious Education (PAI) for the children of migrant workers at Junior High School of SMP Pondok Pesantren Mambaul Ulum. Parental migration abroad evidently shapes the students’ social and psychological conditions, which subsequently influence their religious development as well as their learning motivation. This study employs a qualitative approach utilizing in-depth interviews, participant observation, and documentation techniques. The study involved a total of eight participants: three administrators, three students and two guardians. The data analysis process is inductive in nature, aiming to identify emerging patterns of instructional adaptation derived from empirical findings. Data validity is ensured through source and methodological triangulation, as well as member checking with informants to confirm the accuracy of the interpretations. This study analyzes PAI adaptation using Bronfenbrenner’s Ecological Theory, highlighting integrative curriculum, emotional support and collaborative strategies to strengthen students’ religiosity and learning motivation. The findings of this study reveal three principal conclusions. First, the pesantren develops an integrative approach that harmonizes the formal curriculum with the boarding school culture in order to strengthen the spiritual dimension through the habituation of worship practices and the internalization of religious values in daily life. Second, the institution establishes emotional support systems grounded in both personal mentoring and peer-group assistance to reinforce students’ psychological resilience in maintaining stable learning motivation. Third, collaboration between the school and guardians, the utilization of digital communication, and the implementation of participatory learning methods collectively optimize students’ discipline and religiosity. These findings suggest that the role of PAI within pesantren cannot be confined to formal instruction alone, but must evolve into a relational and context-sensitive practice that meaningfully responds to the lived realities of children growing up in conditions of parental absence.